Capacity Needs Assessment in Transport Innovation Living Labs: The Case of an Innovative E-Mobility Project - Teko, Edmund; Lah, Oliver (Frontiers in Future Transportation, 2022)
Cities around the globe are implementing innovative transport solutions as part of measures to address pertinent socio-economic and environmental challenges in urban areas and help drive the transition to low carbon development. Planning and implementing such solutions require an effective and collective approach that includes the needs and aspirations of all relevant stakeholders. In the planning and implementation of urban transport projects, capacity building components have assumed great significance but seem to be the most eluded activity for project implementers. The Living Lab concept, which allows for co-creation in innovation development, presents the opportunity to adopt innovative participatory approach in capacity building activities in transport projects; and is largely seen as a potential catalyst for rapid transformation to low carbon and sustainability transitions in cities. To this end, this paper highlights the usefulness of the Living Lab approach and provides some perspectives on how key elements of the approach are adapted in the process of assessing the capacity needs of nine (9) cities in planning and implementing e-mobility innovations. The cities are participating in an innovation research project. In the case studied, the project’s capacity needs assessment process was analyzed using an assessment framework built on four (4) key elements of the Living Lab approach, namely: extent of real-life contextualization, level of participation, diversity of stakeholders, and the time span of engagement. Insights from the assessment suggest that relevant project partners and city representatives with diverse expertise were actively involved from the onset and throughout the first five months of the project in defining and refining the capacity needs of partner cities based on local e-mobility conditions. This co-creative process helped determine priority areas where the need for capacity building mostly lied. Designing and operationalizing capacity building interventions tailored to the identified needs, as realized in the project, could therefore help build the necessary capacity and complement other measures aimed at developing e-mobility in the project’s partner cities.